Nursing staff and nursing managers' experiences of using the interRAI ID instrument in assessing the service needs of persons with intellectual disabilities in housing services - Kangasniemi Hanna; Ryhtä Iina; Stolt Minna (WILEY, 2022)
The assessment of service needs among persons with intellectual disabilities (ID) is important to identify a person's needs, strengths and preferences. One commonly used instrument for service needs assessment is Resident Assessment Instrument Intellectual Disabilities (interRAI ID). However, there is limited evidence of the experiences of using interRAI ID for assessing the service needs of persons with ID from nursing staff and nursing managers' perspective. The aim of this study was to explore the suitability of the interRAI ID instrument (version Fi2020.1) for assessing the service needs and functional development of persons with ID as described by nursing staff and nursing managers working in a housing service. The data were collected using focus group interviews (n = 3) in May 2020. The interviews were conducted in units providing housing services for persons with ID (n = 6). The interview groups consisted of nursing staff (n = 22) and nursing managers (n = 6). The data were analysed using inductive content analysis. The experiences of nursing staff and nursing managers fell under three main categories: (1) the assessment process; (2) possibilities to use the assessment data and (3) implementation experience. The interRAI ID instrument is suitable and useful for the systematic assessment of the health, functional capacity and service needs of persons with ID. In the future, effective and evidence-based methods are needed to promote the assessment skills of nursing staff and to use assessment data in nursing practice as well as nursing management.